The political economy of India's fiscal federal system and its reform - M. Govinda Rao; Nirvikar Singh (University of California, Santa Cruz Institute for International Economics (SCIIE), 2006)
This article examines recent and potential reforms in India's fiscal federal system. We summarize key federal institutions in India, including tax and expenditure assignments, and mechanisms for Center-state transfers. We discuss the institutional process by which reforms can and do take place, including the role of academics, political influences, and especially institutions such as the Finance Commission. In contrast to the past, recent commissions have played a greater role in articulating an agenda for fiscal federal reform, which then proceeds through political bargaining. This change has taken place in the context of, and been influenced by, broader economic reform in India.
Keywords: P26; P35; H1; H7; 330; intergovernmental transfers; economic reform; federalism; regional inequalities; Finanzföderalismus; Finanzreform; Finanzausgleich; Regionale Disparität; Wirtschaftsreform; Indien